Inhibiting Polysulfide Shuttle in Lithium–Sulfur Batteries through Low‐Ion‐Pairing Salts and a Triflamide Solvent. (2nd May 2017) - Shyamsunder, Abhinandan; Beichel, Witali; Klose, Petra; Pang, Quan; Scherer, Harald; Hoffmann, Anke; Murphy, Graham K.; Krossing, Ingo; Nazar, Linda F.
Abstract: The step‐change in gravimetric energy density needed for electrochemical energy storage devices to power unmanned autonomous vehicles, electric vehicles, and enable low‐cost clean grid storage is unlikely to be provided by conventional lithium ion batteries. Lithium–sulfur batteries comprising lightweight elements provide a promising alternative, but the associated polysulfide shuttle in typical ether‐based electrolytes generates loss in capacity and low coulombic efficiency. The first new electrolyte based on a unique combination of a relatively hydrophobic sulfonamide solvent and a low ion‐pairing salt, which inhibits the polysulfide shuttle, is presented. This system behaves as a sparingly solvating electrolyte at slightly elevated temperatures, where it sustains reversible capacities as high as 1200–1500 mAh g −1 over a wide range of current density (2C–C/5, respectively) when paired with a lithium metal anode, with a coulombic efficiency of >99.7 % in the absence of LiNO3 additive.